STUDI POTENSI LOW-RESISTIVITY PADA RESERVOAR BATUPASIR LAPANGAN REIRA, FORMASI MENTAWIRBALIKPAPAN GROUP, CEKUNGAN KUTAI, KALIMANTAN TIMUR - , Mohamad Resawan Hakim ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Reira Field is deposited in a fluvio-deltaic environment in the prolific Kutai Basin, in East Kalimantan. For more than 30 years, the majority of the production came from large reservoirs with high-permeability intervals, characterized by standard and near-ideal well log shapes. However, a number of potential pay zones with non-ideal log shapes, including low resistivity reservoirs were initially bypassed leaving significant reserves in the ground. This thesis discusses the reason of the low resistivity zones in the Reira Field, petrophysical correction to obtain optimum saturation water, and identification of potential candidates of low-resististivity pay zones. This research starting by log identification of proven low-resistivity pay zones in Reira Field. Afterwards, integrated analysis of logs, core, thin sections, XRD (conductive minerals and clay minerals identification), SEM, fluid analysis test(MDT), and dipmeter data have been carried out to reveal the reasons of its occurrence in the Reira Field. Presence of illite-smectite as clay minerals and pyrite-siderite-ankerite as conductive minerals become one of the main reasons of low-resistivity occurence in Reira Field. Modification of Rw by pickett plot and utilization of some Sw calculation method have been examined to obtain optimum result of Sw value. At the final stage, identification of mudlog, well log, and fluid analysis test have been conducted in all wells in Reira Field to discover potential candidates across Reira Field. I-72C zone in R-46 well were perforated using the recommendations from the integrated analysis, which have proven these low resistivity zones as hydrocarbon bearing pay zones. Currently, that zones have produced more than 125 MMCFD of gas and are still flowing. Others wells which are R-94 and R- 92 revealed oil and condensate. More than 69 zones have been identified as potential candidatas of low-resistivity pay zones for future perforation.